INVESTIGATION ON AUTOMATED SYSTEM DESIGNS FOR ADHESIVE BONDING OPERATION - KA HEE, CHOONG (2018)
The current manually conducted adhesive bonding process is creating inconsistent quality and inefficiency issues, therefore leading to automation designs of the process, known as Automated Bonding Stations. The purpose of this project is to justify whether the automation approach is better compared to manual operation. Another objective of this project is to compare between 5 Automated Bonding Station designs so that the most suitable design for implementation can be decided. The study is focused on automation in manufacturing using robots, technologies used in automated manufacturing, Dynamic Simulation of designs and also Discrete Event Simulation using manufacturing performance metrics. For the comparison of operating efficiency between manual and automation, MSC ADAMS is used to conduct dynamic simulation of robot arm to determine its time required to complete the operation under maximum angular velocity of 180°/second. Then the comparison between Automated Bonding Station designs will be using WITNESS Software to determine the performance of each design options in 24 hours of operation time. The results of Dynamic Simulation had shown that the robot can replace human operators due to lesser cycle time required in the adhesive bonding process. Simulation result of Discrete Event Simulation using WITNESS Software had also shown that the Automated Bonding Station Design Option 4 is the best in terms of performance.